2015
DOI: 10.1124/mol.115.100891
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Human Cytochrome P450 3A4 and 3A5 by Dronedarone andN-Desbutyl Dronedarone

Abstract: Dronedarone is an antiarrhythmic agent approved in 2009 for the treatment of atrial fibrillation. An in-house preliminary study demonstrated that dronedarone inhibits cytochrome P450 (CYP) 3A4 and 3A5 in a time-dependent manner. This study aimed to investigate the inactivation of CYP450 by dronedarone. We demonstrated for the first time that both dronedarone and its main metabolite N-desbutyl dronedarone (NDBD) inactivate CYP3A4 and CYP3A5 in a time-, concentration-, and NADPHdependent manner. For the inactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
1
19
0
1
Order By: Relevance
“…The common structural features in these antiarrhythmic agents and their metabolites are the alkylamine and furan that are in turn associated with mechanismbased inactivation (MBI) of P450 (Orr et al, 2012). Indeed, corroborating previous findings, our laboratory established the reversible and irreversible inhibition of CYP3A4-and CYP2J2-mediated metabolism of FDA-recommended probe substrates by amiodarone and NDEA (Ohyama et al, 2000;McDonald et al, 2015;Karkhanis et al, 2016) as well as dronedarone and NDBD (Hong et al, 2016;Karkhanis et al, 2016). Independently, amiodarone and dronedarone have been reported as P-gp inhibitors (FDA, 2009b(FDA, , 2012.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…The common structural features in these antiarrhythmic agents and their metabolites are the alkylamine and furan that are in turn associated with mechanismbased inactivation (MBI) of P450 (Orr et al, 2012). Indeed, corroborating previous findings, our laboratory established the reversible and irreversible inhibition of CYP3A4-and CYP2J2-mediated metabolism of FDA-recommended probe substrates by amiodarone and NDEA (Ohyama et al, 2000;McDonald et al, 2015;Karkhanis et al, 2016) as well as dronedarone and NDBD (Hong et al, 2016;Karkhanis et al, 2016). Independently, amiodarone and dronedarone have been reported as P-gp inhibitors (FDA, 2009b(FDA, , 2012.…”
Section: Introductionsupporting
confidence: 84%
“…Rivaroxaban was not tested as a substrate in previous in-house studies investigating the CYP3A4 and CYP2J2 inhibitory potencies of amiodarone, dronedarone, and their metabolites (Hong et al, 2016;Karkhanis et al, 2016). In this study, we observed a significantly slower rate of rivaroxaban clearance by CYP3A4 as compared with CYP2J2 during initial assay optimization (data not published).…”
Section: Discussionmentioning
confidence: 61%
“…Thus, the estimated k inact /K I ratio is nearly 20-fold higher for CYP3A4 compared with CYP3A5, indicating that lapatinib inactivates CYP3A4 to a greater extent than CYP3A5. Other CYP3A substrates, such as dronedarone (Hong et al, 2016), have also been shown to display differences in inactivation characteristics for CYP3A4 and CYP3A5. Time-dependent inhibition of CYP3A4 by lapatinib may be clinically relevant based on previous studies regarding the pharmacokinetics of lapatinib in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers still think CYP3A4 plays a more important role in AFB 1 activation based on the following experimental facts: (i) CYP3A4 is far more abundant than CYP1A2 in the human liver [ 14 ]; (ii) CYP3A4 transforms AFB 1 into exo-8,9-epoxide and a detoxification product AFQ 1 [ 15 ]; and (iii) CYP1A2 metabolizes AFB 1 into detoxification product AFM 1 , exo- and endo-8,9-epoxides [ 15 ], in which endo-8,9-epoxide is not biologically active [ 16 , 17 ]. As the most abundant CYP in the human liver and also the major enzyme responsible for the metabolism of many exogenous and endogenous compounds, CYP3A4 has been studied extensively [ 18 , 19 , 20 , 21 ]. Some CYP3A4 orthologs in other species or tissues have been identified and proved to play the same important roles as human CYP3A4 in AFB 1 activation.…”
Section: Introductionmentioning
confidence: 99%